The anthropologists - Savaş, Ayşegül (Bloomsbury Publishing, 2024)
"From White on White author and frequent New Yorker contributor Aysegül Savas--a warm, elegant, and playful novel of home-hunting and life-building away from one's family of origin. Asya and Manu are looking at apartments, envisioning their future in a foreign city. What should their life here look like? Can they create their own traditions and rituals? Whom can they consider family? As the young couple dreams about the possibilities of each new listing, Asya, a documentarian, spends her days gathering footage from the neighborhood park like an anthropologist observing local customs. "Forget about daily life," chides her grandmother on the phone. "We named you for a whole continent and you're filming a park." Life back in Asya and Manu's respective home countries continues--parents age, grandparents get sick, nieces and nephews grow up--all just slightly beyond their reach. But the world they're making in their new city is growing, too, they hope, into something that will be distinctly theirs. As they open up the horizons of their lives, what and whom will they hold onto, and what will they need to release? Hailed by Lauren Groff and Marina Abramovic, Savas's fine, precise craft turns The Anthropologist's simple apartment search into a soulful, often funny, examination of modern coupledom, home-building, and expat life in the universal modern city" --
Keywords: Belonging (Social psychology) / Fiction; Young adults / Fiction; Real estate management / Fiction; Families / Fiction; Noncitizens / Fiction; Appartenance (Psychologie sociale) / Romans, nouvelles, etc; Jeunes adultes / Romans, nouvelles, etc; Immeubles / Gestion / Romans, nouvelles, etc; Familles / Romans, nouvelles, etc; Psychological fiction; Domestic fiction; Novels; Romans